A Collection of Surveys on Market Experiments 2013
DOI: 10.1002/9781118790700.ch9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on Asset Pricing

Abstract: and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research-You may not further distribute the material or use it for any profit-making activity or commercial gain-You may freely distribute the URL identifying the publication in the public portal Take down policy If you believe that this document breaches copyrigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 66 publications
2
33
0
1
Order By: Relevance
“…As laboratory experimentation allows for a level of control that is unattainable in the field, a rich literature on experimental asset markets has evolved. 1 Bossaerts (2009), Noussair and Tucker (2013), and Palan (2013) review this literature. In most experimental asset markets, trading is limited to a single asset, though some experiments allow for trades in multiple assets (Childs and Mestelman, 2006, Kleinlercher et al, 2014, Duffy et al, 2019 and some studies allow subjects to trade derivative assets (futures, options) on the principal asset of the market (e.g., Forsythe et al, 1982, Friedman et al, 1983, Forsythe et al, 1984, Friedman et al, 1984, Porter and Smith, 1995, Jong et al, 2006, Palan, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…As laboratory experimentation allows for a level of control that is unattainable in the field, a rich literature on experimental asset markets has evolved. 1 Bossaerts (2009), Noussair and Tucker (2013), and Palan (2013) review this literature. In most experimental asset markets, trading is limited to a single asset, though some experiments allow for trades in multiple assets (Childs and Mestelman, 2006, Kleinlercher et al, 2014, Duffy et al, 2019 and some studies allow subjects to trade derivative assets (futures, options) on the principal asset of the market (e.g., Forsythe et al, 1982, Friedman et al, 1983, Forsythe et al, 1984, Friedman et al, 1984, Porter and Smith, 1995, Jong et al, 2006, Palan, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…A major theme in the experimental asset market literature has been the search for means to eliminate mispricing. Short selling, buying on margin, pricing collars, futures markets have all been found to have only limited success in reducing mispricing (King, Smith, Williams, and Van Boening 1993;Haruvy and Noussair 2006;Porter and Smith 1995; Xu 2016; see also Tucker 2013 andPalan 2013 for surveys). Subject sophistication has also been questioned, but King, Smith, Williams, and Van Boening (1993) found that professional traders also generated speculative bubbles (see also Weitzel, Huer, Huber, Kirchler, Lindner, and Rose 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Such consecutive bubbles seem to speed up rather than slow down and subjects (2010), Cheung and Palan (2012), Kirchler et al (2012), Sutter et al (2012), Huber and Kirchler (2012), Cheung et al (2014), Füllbrunn et al (2014b), , Holt et al (2017), Hoshihata et al (2017), and Bosch-Rosa et al (2018). Bossaerts (2009), Noussair and Tucker (2013), Palan (2013), and Nuzzo and Morone (2017) review the literature.…”
Section: Introductionmentioning
confidence: 99%